Microporous structures on mineralized collagen mediate osteogenesis by modulating the osteo-immune response of macrophages - Li, Jun; Luo, Xin; Lv, Zhao-Yong; Qiang, Hui-Fen; Hou, Cai-Yao; Liu, Kun; Meng, Chun-Xiu; Zhang, Yu-Jue; Liu, Feng-Zhen; Zhang, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
It is a new hot pot in tissue engineering and regenerative medicine to study the effects of physicochemical properties of implanted biomaterials on regulating macrophage polarization to promote bone regeneration. In this study, we designed and fabricated mineralized collagen (MC) with different microporous structures via in vitro biomimetic mineralization method. The microporous structures, mechanical properties, shore hardness and water contact angle measurements were tested. Live/dead cell staining, CCK-8 assay, phalloidine staining, staining of focal adhesions were used to detect cell behavior. ELISA, qRT-PCR, ALP, and alizarin red staining (ARS) were performed to appraise osteogenic differentiation and investigated macrophage response and their subsequent effects on the osteogenic differentiation. The results showed that RAW264.7 and MC3T3-E1 cells were able to survive on the MC. MC with the microporous structure of approximately 84 μm and 70%–80% porosity could promote M2 macrophage polarization and increase the expression level of TGF-β and VEGF. Moreover, the gene expression of the osteogenic markers ALP, COL-1, and OCN increased. Therefore, MC with different microporous structures mediated osteoimmunomodulation in bone regeneration. These data will provide a new idea of biomaterials inducing bone repair and direct the optimal design of novel immune biomaterials, development, and rational usage.